Lower rate of selected congenital heart defects with better maternal diet quality: a population-based study. Issue 1 (24th August 2015) - Botto, Lorenzo D; Krikov, Sergey; Carmichael, Suzan L; Munger, Ronald G; Shaw, Gary M; Feldkamp, Marcia L
Abstract : Objective: To evaluate whether better diet quality in mothers is associated with lower risk for major non-syndromic congenital heart defects in their children. Design: Multicentre population-based case–control study, the National Birth Defects Prevention Study. Setting: Ten sites in the USA. Participants: Mothers of babies with major non-syndromic congenital heart defects (n=9885) and mothers with unaffected babies (n=9468) with estimated date of delivery from 1997 to 2009. Main outcome measures: Adjusted ORs for specific major congenital heart defects by quartiles of maternal diet quality in the year before pregnancy, assessed by the Diet Quality Index for pregnancy (DQI-P) and the Mediterranean Diet Score. Quartile 1 (Q1) reflecting the worst diet quality and Q4 the best diet quality. Results: Better diet quality was associated with reduced risk for some conotruncal and atrial septal heart defects. For DQI-P, estimated risks reductions (Q4 vs Q1) for conotruncal defects were 37% for tetralogy of Fallot (OR 0.63, 95% CI 0.49 to 0.80) and 24% overall (OR 0.76, 95% CI 0.64 to 0.91); and for septal defects, 23% for atrial septal defects (OR 0.77, 95% CI 0.63 to 0.94) and 14% overall (OR 0.86, 95% CI 0.75 to 1.00). Risk reductions were weaker or minimal for most other major congenital heart defects. Conclusions: Better diet quality is associated with a reduced occurrence of some conotruncal and septal heart defects. This finding suggests that a reduction in certain cardiac malformations may be an additional benefit of improved maternal diet quality, reinforcing current preconception care recommendations.